Meningkatkan Sikap Tanggung Jawab Anak Usia 5-6 Tahun di Paud Kasih Filadelfia Nias Melalui Metode Proyek - Panggabean, Ruth Donda Eleonora; Panni Ance L.Tobing; Laia , Yustito Albert (Universitas Sari Mutiara Indonesia, 2023)
The purpose of this research is to improve the Attitude of Responsibility of Children Aged 5 -6 Years at Kasih Filadelfia Kindergarden Nias through the Project Method. This research is Classroom Action Research (PTK). The research data was obtained through observations conducted in 2 cycles where each cycle contained 2 meetings. Research results in Cycle I obtained 1 (6.67%) children in the BB category (Not yet developed), 12 (86.67%) children in the MB category (Beginning to Develop) and the average value was 49.78%. In Cycle II there was an increase of 80% of the children reaching the BSB (Very Well Developed) category and 20% of the children were in the BSH (Developing According to Expectations) category with an average value of 93.73%. Based on the indicators of the level of achievement of an increased attitude of responsibility, if 76% of the total number of children has reached the BSB category, the research will stop in cycle II. So it can be concluded that Attitude of Responsibility of Children Aged 5 -6 Years at Kasih Filadelfia Kindergarden Nias Increasing through the Project Method.